The Relationship between P-Wave Morphology and Atrial Fibrillation - Al-Dahan, Ziad T.; Al-Hashimi, Abbas F.; Al-Asady, Natiq A. (Al-Nahrain Journal for Engineering Sciences, 2017)
The objective of this paper is to develop an efficient P-wave detection algorithm based on the morphology characteristics of arrhythmias using time domain analysis.ECG from normal subjects, and patients with atrial fibrillation were studied. After baseline wander cancellation, power line interference filtration, the step of QRS detection using the pan- Tompkins algorithm is utilized to calculate R peak which represent the reference point to detect P peak.The algorithm was tested with experiments using MIT-BIH arrhythmia database which included Paroxysmal Atrial Fibrillation PAF prediction challenge, Massachusetts Institute of Technology MIT-BIH normal sinus rhythm, long term Atrial Fibrillation AF and MIT-BIH atrial fibrillation where every P-wave was extracted.The results reveal that the algorithm is accurate and efficient to detect and classify arrhythmias resulted from atrial fibrillation.